Pengaruh Model Pembelajaran Kooperatif Tipe Write Around Terhadap Keterampilan Menulis Teks Negosiasi Siswa Kelas X SMA Negeri I Simpang Empat Kabupaten Karo Tahun Pembelajaran 2022/2023 - Sidabutar, Arna Adestra (Medan Resource Center, 2023)
This research investigates the impact of the Write Around cooperative learning model on the ability to write negotiation texts among class X students at SMA Negeri 1 Simpang Empat, Karo Regency. The population includes all class X students, with a random sample of 34 students. The study employs a Pre-Experimental Design with a one group pre-test post-test approach using Cluster Random Sampling. The research instrument consists of structured components (orientation, request, fulfillment, offer, agreement, purchase, closing) and linguistic rules (news sentences, questions, commands, hope sentences, conditional sentences, causal conjunctions, spelling). Data analysis includes normality, homogeneity, and hypothesis tests. Pre-test scores averaged 60 (poor category), while post-test scores averaged 88 (very good category). Normality test results show Lcount < Ltable for both pre-test (0.094 < 0.300) and post-test (0.078 < 0.381) data. The homogeneity test yielded Fcount < Ftable (2.66749 < 8.94065). Hypothesis testing indicated Tcount > Ttable (15.10 > 2.03693), rejecting the null hypothesis and accepting the alternative hypothesis. The data results are normally distributed, concluding that the Write Around cooperative learning model significantly enhances the ability to write negotiation texts among class X students at SMA Negeri 1 Simpang Empat, Karo Regency.